2020
DOI: 10.1038/s41598-020-75666-6
|View full text |Cite
|
Sign up to set email alerts
|

Dual antiplatelet therapy reduced stroke risk in transient ischemic attack with positive diffusion weighted imaging

Abstract: Dual antiplatelet therapy (DAPT) reduced stroke risk in high-risk transient ischemic attack (TIA) patients assessed by ABCD2 score. Patients with positive diffusion-weighted imaging (DWI) were identified as imaging-based high-risk. The present study aims to investigate whether DAPT could reduce stroke risk in TIA with DWI positive. The study enrolled TIA patients within 72 h of onset from the prospective TIA database of the First Affiliated Hospital of Zhengzhou University. The predictive outcome was ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, the tool is effective at helping prevent stroke because it identifies those at high risk effectively and therefore allows earlier implementation of stroke prevention strategies beyond simply controlling blood pressure and diabetes, including lipid profiling, cardiac monitoring, carotid imaging and considering dual antiplatelets. 78 …”
Section: Discussionmentioning
confidence: 99%
“…However, the tool is effective at helping prevent stroke because it identifies those at high risk effectively and therefore allows earlier implementation of stroke prevention strategies beyond simply controlling blood pressure and diabetes, including lipid profiling, cardiac monitoring, carotid imaging and considering dual antiplatelets. 78 …”
Section: Discussionmentioning
confidence: 99%
“…There is a possible increased risk of developing hemorrhagic events with DAPT treatment over a 7 International Journal of Vascular Medicine prolonged period of time. A number of research studies have found that DAPT's use of aspirin and clopidogrel, like a 21day use period, reduces the risk of hemorrhagic transformation [105][106][107][108]. Further research is indicated to analyze the effectiveness of DAPT and its optimal therapy duration in high-risk stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pei et al analyzed the effect of DAPT and MAPT on stroke risk in TIA patients through positive diffusion-weighted imaging (DWI) [ 107 ]. Researchers found that TIA patients on MAPT had a higher 90-day stroke risk than patients that used DAPT (23.7% vs. 13.4%, p = 0.029).…”
Section: Use Of Antiplatelets In Ischemic Stroke and Hemorrhagic Transformation: Mono-antiplatelet (Aspirin) Versus Dual-antiplatelet (Asmentioning
confidence: 99%
See 2 more Smart Citations